Factors Influence Customer Churn on Internet Service Provider in Indonesia - Handi Aulia Triyafebrianda; Nila Armelia Windasari (Universitas Airlangga, 2022)
Rapid growth of internet users in Indonesia and the Covid-19 pandemic situation has prompted the emergence of new Internet Service Providers in line with the increasing demand for internet access. Several new internet service providers are emerged leading to a more competitive environment. Churn in subscription model business become important variable since the brand of internet service provider increasing. The purpose of this study is to examine factors influence customer churn in internet service provider so company can resolve and anticipate the churn problems. By using the method SEM-PLS to 102 respondents data collected, it was concluded that customer churn was significantly influenced by complaint management and multi-brand attitude. Another result is the tendency of multi-brands attitudes moderates the price which is significantly related to customer churn.